The process of teaching mathematics learning: an analysis of student / O processo de ensino aprendizagem da matemática: uma análise do aluno - osé Erlandson Kaique Lima dos Santos; Gêrlan Cardoso da Silva (Universidade Estadual de Alagoas, 2016)
This paper aims to analyze how Possible Causes of the difficulties in the process of Teaching and Learning of Mathematics at school Students of Vision a state of the city of Arapiraca/AL. Viewpoint of through these, we believe what is in the interaction que as social relations become concrete. Then is search search watch and confront how not causes learning in mathematics in student view. In first time, we apply some questionnaires in the classroom paragraph of students where they answered questions regarding the difficulties in the process of teaching and learning, about the methodological approaches to teacher and because of you're not like the discipline. no second time analyzing os data paragraph confront after the results and finally present as answers, graph, paragraph one get a conclusion about (s) to factor (s) que impede An Effective learning of mathematics in the classroom. Authors How Freire (1988), Chalita (2001), Cotrim (1987), and Other substantiate this search